Pengaruh Work Family Conflict dan Disiplin Kerja terhadap Kinerja Karyawan pada BPR Duta Bali - Pratiwi, Ni Komang Wiwin (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
One of the main aspects of management work related to human resources is the aspect related to employee performance. The population in this study were all employees of BPR Duta Bali as many as 45 people. Determination of the sample using saturated sampling. After the instrument test and classical assumption test were carried out, the data was analyzed using multiple linear regression, analysis of determination, t test, and F test.The test results show that the negative and significant effect of work family conflict on employee performance. Positive and significant influence of work discipline on employee performance. Simultaneous effect of work family conflict and work discipline on employee performance. It can be concluded that the lower the level of work family conflict and the higher the level of work discipline, it can improve employee performance at BPR Duta Bali. It is recommended to BPR Duta Bali to be able to improve employee performance by paying attention to the level of work family conflict and work discipline that they currently have in order to maximize their performance.